Governance, Fragility, and Conflict : Reviewing International Governance Reform Experiences in Fragile and Conflict-Affected Countries - Agborsangaya-Fiteu, Ozong (World Bank, Washington, DC, 2017)
This report seeks to inform the development of a framework for addressing governance reform in fragile and conflict affected environments through are view of international experiences. The report analyzes the experience both of countries that sustained a transition to peace and those that fell back into conflict. Pertinent lessons will be drawn selectively from a range of fragile and conflict affected countries, including Haiti, Cambodia, Bosnia and Herzegovina, Mozambique, Liberia, Timor-Leste, Afghanistan, Rwanda, Indonesia, Sierra Leone, and Angola. No specific typologies have been adopted or formed in order to assess these lessons, because typologies can be limiting and experiences can be better assessed based on the specificity of each country's context. The first section of the report sets out broadly accepted definitions of key terms such as governance, state building, and fragility. The second section reviews experiences with diverse governance dimensions and explores the objectives, opportunities, and constraints associated with each.